Sociolinguistic Perception Regarding Urban/Rural Local Dialects in the Province of Melipilla - Céspedes, Macarena (2023)
The main objective of this sociolinguistic research is to trace various perceptions regarding intonational variation in different localities from rural and urban contexts in the province of Melipilla, Metropolitan Region. The methodology incorporated an ethnographic approach to the different localities, where a perception survey was administered to 87 subjects —both men and women— between the ages of 18 and 70.This article presentsthe most relevant results regarding perceptions and self-perceptions about specific language uses in these communities and their spoken identity, understanding that these entities are becoming closer to each other due to the increasing urbanization of rural areas near Santiago, Chile (Céspedes 2017).